Strengthening research administration in low-resource settings: assessment of knowledge gain from a research administration workshop at Makerere University, Uganda - Elizabeth N. Christian; Harriet Nambooze; Bethany Ekesa; Peruth Ainembabazi; Sylvia Antonia Nakimera Nannyonga-Tamusuza; Mordecai Tayebwa; Kate Klein (Health Research Policy and Systems, 2026)
Abstract Background This manuscript will focus on a research administration skills-building workshop as part of a National Institutes of Health (NIH) G11 grant for administrative development, “Expanded Strengthening of Makerere University’s Research Administration Capacity Program (E-SMAC)”. E-SMAC is a partnership between Makerere University, Uganda and Northwestern University, United States of America. Research administrators (RAs) have grown in both specialization and importance within the university setting as their administrative expertise increases the likelihood of adherence to solicitation requirements and thereby ultimately increases the likelihood of obtaining funding from competitive funding opportunities. There are common skill sets that are required across sponsors and funding opportunities regardless of institutional structure, yet methods for training RAs in fundamental grants management within the low- to middle-income countries (LMIC) setting have not been examined. This study assessed the core skills and learning outcomes of a RA skills-building workshop at Makerere University in Uganda. Methods The in-person workshop, consisting of oral presentations, hands-on workshops and group discussions, lasted 4 days. Daily pre- and post-tests were administered to participants. Attendees were both research faculty and staff who support grants management functions at Makerere University and 10+ peer institutions across Uganda. The test consisted of true/false, multiple-choice and knowledge confidence questions. The participants’ evaluations were matched through codes and analysed for individual change. Results The analysis of change in knowledge for true/false and multiple-choice questions showed mixed results. Some categories showed significant change, whilst others showed no change or participants answered the post-test questions incorrectly. No change may be from participants already knowing the answers or from guesswork on evaluations. Heat maps for the self-reported knowledge change showed overall positive movement, with participants’ knowledge increasing and each category showing statistically significant self-reported knowledge gain and a P -value smaller than 0.001. Whilst the self-reported knowledge change showed statistical significance, analysis of the change in knowledge through multiple choice and true/false allows for examination of differences in workshop content for each topic area and overall evaluation structure. Conclusions Findings suggest that workshop trainings can strengthen RA knowledge in areas of pre-award, post-award, compliance and financial management of grants. Improving RA skills at local universities in LMIC settings is important to ensure research projects receive appropriate administrative support. Evaluating the methods used to teach these skills and providing effective, sustainable models will help sustain global health research as the landscape continues to evolve.